PELUANG USAHA INOVASI PUPUK TULANG TERNAK DAN CANGKANG TELUR UNTUK PERTANIAN BERKELANJUTAN - Ratih Apri Utami; Anarofida Anarofida; Meihilda Hoda Pratiwi; Rizky Bangkit Pamungkas; Sapna Dwi Elisa; Ubaidillah Ubaidillah (Politeknik Negeri Semarang, 2022)
Food is one of the needs consumed by humans every day to support survival. Food consumed by humans certainly produces waste from unused food waste. The existence of livestock bones and egg shells that are abundant in the community as food waste from animal materials can be used for organic fertilizer. The effective content of the waste can support the completeness of fertilizer nutrients applied to plants.